The Psalms as Christian praise: a historical commentary - Waltke, Bruce K. (Eerdmans B. Publishing Company, 2019)
"Completes a trilogy of exegetical volumes on the Psalms, following up on The Psalms as Christian Worship and The Psalms as Christian Lament. Examines twelve praise psalms, each including a translation, commentary, and how the psalm was interpreted in the Christian tradition. Intended especially for preachers and students of Psalms"--